Tetralogy Scalp Block Anesthesia without Opioid for Anesthetic Management in Children Undergoing Frontal Reconstruction - Mahendratama, Muhammad Riza; Prihatno, M. Mukhlis Rudi; Wicaksono, Nugroho (Jurnal Neuroanestesi Indonesia, 2024)
Traumatic brain injury (TBI) is one of the leading causes of death in developing countries, especially Indonesia. The incidence of TBI in Indonesia between 6% and 12% and has a mortality rate of 25% to 37%. Treatment of traumatic brain injury is done as soon as possible to improve quality of life and prevent further damage to brain cell and function. A 13-year-old child sustained mild traumatic brain injury and frontal fracture due to a fall from a motorcycle. The patient underwent frontal reconstruction in the operating room. The surgery was performed under regional anesthesia using a scalp block with an ultrasound device and without using opioid drugs. The surgery lasted about two hours without hemodynamic disturbances. The post-surgery Visual Analogue Scale (VAS) was 2-3. The patient was observed in the regular ward for four days and discharged without any disability. Scalp block was chosen to enhances analgesic quality without opioid, reduce requirement of ICU as well as hospitalization time, and save treatment costs. Opioids may cause respiratory and gastrointestinal depression and Postoperative Nausea and Vomiting (PONV).